HIV replication is associated to inflammasomes activation, IL-1ß, IL-18 and caspase-1 expression in GALT and peripheral blood (2018)
Background Human immunodeficiency virus (HIV) promotes an inflammatory process, leading to the progressive loss of the functional capacity of the immune system. The HIV infection induces alterations in several tissues, but mainly in the gut-associated lymphoid tissue (GALT). However, the degree of GALT deterioration varies among infected individuals. In fact, it has been shown that HIV-controllers, who spontaneously control viral replication, exhibit a lower inflammatory response, and a relative normal frequency and function of most of the immune cells. Inflammasomes are molecular complexes involved in the inflammatory response, being NLRP1, NLRP3, NLRC4, AIM2 and Pyrin inflammasomes, the best characterized so far. These complexes regulate the maturation of cytokines of the IL-1 family, including IL-1ß and IL-18. These cytokines have been associated with immune activation and expansion of HIV target cells, promoting viral replication. Interesting, some reports indicate that HIV induces the activation of the NLRP3 inflammasome, but the role of this, and other inflammasomes during HIV infection, especially in GALT, remains unclear. Objective To compare the relative expression of inflammasome components and the proinflammatory response related to their activity, between HIV-progressors and HIV-controllers. Methods GALT biopsies and peripheral blood mononuclear cells (PBMCs) from 15 HIV-controllers and 15 HIV-progressors were obtained. The relative expression of the following inflammasome components were evaluated by RT-PCR: NLRP3, NLRC4, NLRP1, AIM2, ASC, Cas-pase-1, IL-1ß and IL-18. In addition, plasma concentration of IL-18 was evaluated as an indicator of baseline proinflammatory status. Finally, in supernatants of PBMCs in vitro stimulated with inflammasome agonists, the concentrations of IL-1ß and IL-18 were quantified by ELISA. © 2018 Feria et al. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.